Exploring the multitude of Muslims in Europe : essays in honour of Jørgen S. Nielsen - Nielsen, Jørgen S.; Vinding, Niels Valdemar; Račius, Egdūnas; Thielmann, J. (Jörn) (Muslim minorities., 2018)
A number of friends and colleagues of Jørgen S. Nielsen have joined together to celebrate his life and work by reflecting his more than forty years of scholarly contributions to the study of Islam and Muslims in Europe. The fourteen articles move through conceptualisations, productions and explorations of the multitudes of Muslims in Europe, and the authors draw on Nielsen's own work on the history and challenges of the Muslim community in Europe, critical thinking, ethnicities and theologies of Muslims in Europe, Muslim minorities, Muslim-Christian relations, and on Islamic legal challenges in Europe.